2018
DOI: 10.1002/ase.1797
|View full text |Cite
|
Sign up to set email alerts
|

The design and evaluation of a master of science program in anatomical sciences at Queen's University Canada

Abstract: The purpose of this study was to describe the design and evolution of a unique and successful Master of Science program in anatomical sciences at one Canadian post-secondary institution and to evaluate its long-term impact on student learning. This program prepares students to teach anatomy and design curricula in the anatomical sciences and is structured around three pillars of competency-content (disciplinary knowledge and transferable skills), pedagogy, and inquiry. Graduates of the program from the last te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The programs that experienced the smallest decrease in allocated time to cadaver‐based modalities were anatomy graduate, dental, physician assistant, nursing, and graduate health. Most of these programs typically have a lower enrollment (i.e., less than 100 students on average) (Brokaw & O’Loughlin, 2015; Kolomitro et al, 2018; PAEA, 2019; CODA, 2020) than medical schools and undergraduate programs as a whole (Schutte, 2016; Attardi et al, 2018; AAMC, 2020), allowing for proper physical distancing, which may explain why the decrease in cadaver‐based modalities was not as extreme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The programs that experienced the smallest decrease in allocated time to cadaver‐based modalities were anatomy graduate, dental, physician assistant, nursing, and graduate health. Most of these programs typically have a lower enrollment (i.e., less than 100 students on average) (Brokaw & O’Loughlin, 2015; Kolomitro et al, 2018; PAEA, 2019; CODA, 2020) than medical schools and undergraduate programs as a whole (Schutte, 2016; Attardi et al, 2018; AAMC, 2020), allowing for proper physical distancing, which may explain why the decrease in cadaver‐based modalities was not as extreme.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomy educators may also have been eager to return to in-person cadaver-based laboratories due to their long-standing beliefs that learning is facilitated by hands-on experiences, and that working with body donors fosters humanistic personal growth (Harmon et al, 2021) and the formation of professional identity (Barash et al, 2021). Concurrently, with the increase of cadaveric modalities during August-December compared to during May-August (Harmon et al, 2021), there was a decrease in the utilization of "other" modalities from 50.5% to 33.7%, but the use of plastic modalities was & O'Loughlin, 2015;Kolomitro et al, 2018;PAEA, 2019;CODA, 2020) than medical schools and undergraduate programs as a whole (Schutte, 2016;Attardi et al, 2018;AAMC, 2020), allowing for proper physical distancing, which may explain why the decrease in cadaver-based modalities was not as extreme.…”
Section: Laboratory Teachingmentioning
confidence: 99%
“…(4) In the aspect of interaction, the findings were: ease of accessing online learning services, 12% stated that it was not good, the quality of giving comments by lecturers to academic discussion forums that had been carried out in online learning, it was found that 6% said it was not good. (5) In the evaluation aspect, the following findings were obtained: the clarity of the assessment rubric of the assignment given by the lecturer, it was obtained that 12% stated that it was unclear, the scoring service for the assignment that had been given by the lecturer to students through online was 6% less well [10].…”
Section: Resultsmentioning
confidence: 99%
“…There is a view that explains that the teacher is a great, meritorious figure, even a hero who is often called an unsung hero. With this predicate, the teacher is a great figure who will never lose his instinct, his adrenaline to educate and raise education [5].…”
Section: Introductionmentioning
confidence: 99%
“…Total answers (n = 123) 16,23 . The strategies to teach anatomy focusing on "how to approach" are based on the pedagogical process, which helps to identify study strategies that challenge and recognize weaknesses, as well as take advantage of strengths 17,24,25 . G2 was the main group to state in Q7 that the seven strata method is "didactic" and "comprehensible".…”
Section: Discussionmentioning
confidence: 99%